Evil for Flannery O’Connor - Peña Vial, Jorge (Mercurio Peruano, 2020)
This author’s great theme is his remarkable theological vivid description of evil, its corrosive action varied, and the many disguises behind which it is hidden. His stories revolve around criminal activity, violent and grim, the characters are rooted in sin, are refined perverse or openly satanic. Despite the cold cruelty and implacable hardness, reveals a new order of existence, a sudden conversion, shining truth that dispels the darkness of error and sin and shows us the calm face and clear reality.